An agenda for psychological distance apart from construal level. Issue 8 (29th June 2020) - Maglio, Sam J.
Abstract: Mental life is not confined to physical reality. Instead, anchored in the here and now, people can conjure worlds set in other locations, in other times, from other people's perspectives, and with otherworldly odds. These routes away from immediacy represent different dimensions of psychological distance—space, time, social distance, and probability—in that they all provide a means by which targets of consideration can feel psychologically distant. Though largely developed under the theoretical banner of construal level theory, psychological distance benefits from consideration in its own, independent right. This review proposes that prominent characteristics of it inform an agenda for translational insights across the four dimensions of psychological distance.